Achieving sustainable competitive advantage: The case of small and medium-sized enterprises in Botswana - Tadios Munodawafa; Micheline Juliana Alberta Naude; Krishna Kistan Govender (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration, 2024)
Despite their importance, SMEs experience a low survival rate. For example, in Botswana, 60% of SMEs fail to survive within their first 18 months of operation and an additional 30% over the next 12 months. Within this context, this article aims to investigate factors that impact the sustainable competitive advantage of SMEs in Botswana. Primary data were gathered through seven in-depth interviews with key government informants based on a purposive sampling technique, and thematic analysis was used to analyse the data. The findings reveal that manufacturing enterprises in Botswana are high-risk enterprises, and financial institutions are reluctant to provide them with funds. Furthermore, some of the challenges SMEs face are high rentals, high cost of land (space), equipment, product quality, traceability issues, and mileage charges in the countries where they export their products. Recommendations include that funding organisations review issues of collateral to increase access to finance for SMEs and that the government promotes joint ventures between multinational corporations, as this would result in the transfer of funds, technology, and skills. The registration of patents and use of indigenous raw materials by manufacturing SMEs will help to accelerate innovation and creativity and drive down production costs, thus increasing the survival and sustainable competitive advantage of these firms.